2018
DOI: 10.1080/17436753.2018.1464271
|View full text |Cite
|
Sign up to set email alerts
|

The colour of monolithic zirconia restorations determined by spectrophotometric examination

Abstract: Objective: The aim of this in vitro study is to examine the optical effects of monolithic zirconia of different translucency and thickness, combined with substrates of different colours. Materials and methods: Zirconia specimens of two colours (A2P1, WHITE) were used for the study, three try-in pastes (Variolink Esthetic); substrates were prepared from nine types of materials (six VITA SIMULATE, three metals). Measurements were carried out at the Faculty of Atomic Physics of the Technical University of Budapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The graph suggested a substantial variability in Δ E across substrate materials combined with ceramic layers in the lower thickness range (0.5–1.0 mm); however, at the mid- and high-range (1.5–2.5 mm) substrate colour was less influential. The Δ E value for the reference sample was zero, confirming the precision of the measurement [15].
Figure 4 Different zirconia (P1) layer thickness combined with different substrate materials.
…”
Section: Resultsmentioning
confidence: 60%
“…The graph suggested a substantial variability in Δ E across substrate materials combined with ceramic layers in the lower thickness range (0.5–1.0 mm); however, at the mid- and high-range (1.5–2.5 mm) substrate colour was less influential. The Δ E value for the reference sample was zero, confirming the precision of the measurement [15].
Figure 4 Different zirconia (P1) layer thickness combined with different substrate materials.
…”
Section: Resultsmentioning
confidence: 60%
“…A Semmelweis Egyetem Fogpótlástani Klinikája 2013 óta vizsgálja a különböző kerámiák optikai tulajdonságait [1,2,7]. A vizsgálatok célja kimutatni, hogy a különböző színű csonkok hogyan befolyásolják a restau rá tum végleges színét a kerámia vastagsága és transz lu cenci á ja, valamint a ragasztócement optikai tulajdonságainak függvényében.…”
Section: Bevezetésunclassified
“…In the case of all-ceramic systems, several studies have examined factors affecting the esthetics of the final restoration, such as the color of the abutment, the thickness and translucency of the ceramic, and the color and layer thickness of the luting cement. [18][19][20][21][22][23][24][25][26][27][28][29][30] During the examination of lithium-disilicate glass ceramics, it was found that the color of the abutment, the thickness of the ceramic and the color of the cement significantly influence the color of the restoration. 18,20 Regarding the final appearance of monolithic zirconia restorations, studies emphasize the effect of abutment color, ceramic thickness, and their combined effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of materials with translucent properties, the appearance of the restoration is not determined solely by its material, but by everything that is located behind or under it. In the case of all‐ceramic systems, several studies have examined factors affecting the esthetics of the final restoration, such as the color of the abutment, the thickness and translucency of the ceramic, and the color and layer thickness of the luting cement 18–30 . During the examination of lithium‐disilicate glass ceramics, it was found that the color of the abutment, the thickness of the ceramic and the color of the cement significantly influence the color of the restoration 18,20 .…”
Section: Introductionmentioning
confidence: 99%